Molecular regulatory mechanisms and nursing preventive measures of depression-related thrombosis risk - Fang, Jing; Shen, Qunyan; Lv, Xinghui (Edelweiss Applied Science and Technology, 2025)
Depression, affecting over 280 million individuals globally, is increasingly linked to heightened thrombosis risk through molecular pathways such as inflammatory cytokine activation, platelet hyperreactivity, and endothelial dysfunction. This systematic review aims to explore the biological mechanisms of depression-induced thrombosis and assess the impact of nursing-led preventive measures. A structured search of PubMed, ScienceDirect, CINAHL, Google Scholar, and Web of Science was performed, identifying 40 high-quality studies for meta-analysis. Key findings indicate that endothelial dysfunction (Cohen’s d = 0.81, β = 0.499, p < 0.001) emerged as the strongest predictor of thrombosis, followed by inflammatory markers (Cohen’s d = 0.78, β = 0.438, p < 0.001) and platelet aggregation (Cohen’s d = 0.65, β = 0.363, p < 0.001). Although nursing interventions (β = 0.069, p = 0.139) demonstrated limited direct effect, their role in early screening, lifestyle modifications, and adherence monitoring remains crucial. The study underscores the need for interdisciplinary strategies, integrating psychiatric, cardiovascular, and nursing care to mitigate thrombotic risk in depression. Practical implications highlight the importance of routine thrombosis screening and structured nursing interventions in psychiatric settings to enhance patient outcomes. Further research should focus on biomarker-guided preventive strategies and randomized controlled trials to validate these findings.